2003
DOI: 10.1097/01.prs.0000070989.23469.1f
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Initial Recurrence and Prognosis after Sentinel Lymph Node Biopsy and Selective Lymphadenectomy for Melanoma

Abstract: The histologic status of the sentinel lymph node is a highly significant prognostic factor for patients with clinically localized cutaneous melanoma. The patterns of initial treatment failure of patients with positive sentinel lymph node biopsy versus those with negative results have not been well described. The purpose of this study was to determine the relative prognostic importance of sentinel lymph node status and to compare patterns of initial treatment failure and prognosis of node-positive versus node-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 27 publications
8
39
2
1
Order By: Relevance
“…Morton et al reported the sensitivity rate of SLNB as 95.3% overall: 99.3% for the groin, 95.3% for the axilla, and 84.5% for the neck basins (15). Reported rates of SN metastasis are 12 to 20% for 1-to 2-mm melanomas, 28 to 33% for 2-to 4-mm melanomas, and 28 to 44% for melanomas thicker than 4 mm (16).…”
Section: Sentinel Node Sensitivity and Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Morton et al reported the sensitivity rate of SLNB as 95.3% overall: 99.3% for the groin, 95.3% for the axilla, and 84.5% for the neck basins (15). Reported rates of SN metastasis are 12 to 20% for 1-to 2-mm melanomas, 28 to 33% for 2-to 4-mm melanomas, and 28 to 44% for melanomas thicker than 4 mm (16).…”
Section: Sentinel Node Sensitivity and Specificitymentioning
confidence: 99%
“…The landmark Multicenter Selective Lymphadenectomy Trial-I (MSLT-I) is the largest trial comparing the use of SLNB and elective lymph node dissection (ELND) to observe patients with intermediate thickness melanomas in determining prognosis and its impact on survival (15,22). Long-term data from the MSLT-I show improved 10-year disease-free survival but fail to show improved melanoma-specific survival (22).…”
Section: The Multicenter Selective Lymphadenectomy Trialmentioning
confidence: 99%
“…With long-term follow-up of patients with negative sentinel nodes there is a small but definite incidence of recurrence in the mapped and sampled nodal basin. 5,[10][11][12][13][14][15][16][17][18][19] These patients may be considered to have a false-negative result of their sentinel node biopsy procedure. Previous reports have suggested that the majority of patients who recur in the relevant node field will, in fact, have identifiable metastases in the biopsied sentinel node if a more comprehensive histopathologic evaluation of the node is undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…With long-term follow-up of patients with negative sentinel nodes, some develop a recurrence in the mapped and sampled nodal basin and these patients may be considered to have a false-negative result of their sentinel node biopsy procedure. A technique to confirm true sentinel node identity may reduce the false-negative rate of the procedure, which has been disappointingly high (up to 44%) in several recently reported studies, 5,[10][11][12][13][14][15][16][17][18][19] or at least provide a retrospective explanation for a falsenegative result.…”
mentioning
confidence: 99%
“…A positive SLNB has been shown to be the best predictor of recurrence and survival in patients with clinically node-negative cutaneous melanoma (Wagner, Ranieri et al 2003). Patient mean charges for SLNB and wide excision alone respectively are $12,193 and $1,466 (Agnese, Abdessalam et al 2003).…”
Section: Breslow Index As the Primary Predictive Factor Of Sentinel Lmentioning
confidence: 99%